(x - 6)(x - 4) = x(x - 4) - 6(x - 4) = x^2 - 4x - 6x + 24 = x^2 - 10x +24

(x - 8)(x - 5) = x(x - 5) - 8(x - 5) = x^2 - 5x - 8x + 40 = x^2 - 13x + 40

(x + 7)(x - 7) = x(x - 7) + 7(x - 7) = x^2 - 7x + 7x - 49 = x^2 - 49

(x + 3)(x - 3) = x(x - 3) + 3(x - 3) = x^2 - 3x + 3x - 9 = x^2 - 9

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up